Analisis Event Marketing Tabungan Tandamata Dalam Meningkatkan Jumlah Nasabah Di Bank Bjb Kantor Pusat Bandung - Mega Putri; Chandra Hendriyani; Tengku Sitti Rochmah (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
In today's competitive era of inter-bank competition, companies must be able to adjust the right marketing strategy, because everything is done to maintain the company's existence. Banks are financial institutions that collect funds from the public and then channel them back through credit. To attract consumers or prospective customers, Bank bjb's head office conducts event marketing promotions through concerts by inviting various top artists. It is hoped that this will become an attraction for prospective Bank bjb customers. The purpose of this study was to determine the success of the event marketing of the Tandamata savings and the DIGI Cash Application, in increasing the number of customers at Bank bjb's head office. The research method used is qualitative, with a descriptive approach through interviews and direct observation. The results of the study show that the strategy used by Bank bjb has been effective, as evidenced by the increasing number of Tandamata savings customers, the procedure for opening Tandamata savings can run well, reflected in the convenience provided by Bank bjb to customers. However, for a good marketing event, it must be able to influence the number of customers who open bjb Tandamata savings at bank bjb.